Interagency Collaboration for Pediatric Autism Spectrum Disorder: Perspectives of Community-Based Providers - Azad, Gazi (J Interprof Educ Pract, 2021)
BACKGROUND: Interagency collaboration between community and school settings is one mechanism to serve the complex needs of pediatric patients with autism spectrum disorder (ASD). PURPOSE: We surveyed a national sample of community-based providers to examine their perspectives on interagency collaboration with school-based providers when serving pediatric patients with ASD. METHOD: Medical and behavioral/mental health professionals practicing in community settings were recruited. Participants (N = 116) completed an online survey about their interagency collaboration experiences with schools. RESULTS: The majority of the sample reported engaging in interagency collaboration with school-based providers; however, the frequency was limited and was associated with the number of years working in the field. Community-based providers wanted more didactic and hands-on experiences in collaboration. Barriers and facilitators were related to schools’ administration, school personnels’ training in ASD, information exchange, and delineating between identification systems. DISCUSSION AND CONCLUSION: Our findings highlight the importance of leadership support and the need for innovative training experiences to support school-community interagency collaboration.